Preparation method and application of semiconducting strontium titanate ceramic

Through the method of niobium element doping and nitrogen treatment, the flexural electrical properties of semiconductor strontium titanate ceramics are improved, the problem of low flexural electrical properties in the prior art is solved, and the applicability of ceramic materials in extreme environments and precision applications is realized.

CN119751053APending Publication Date: 2025-04-04XI AN JIAOTONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411973352.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The semiconductor strontium titanate ceramics prepared in the prior art have low flexural electrical properties and are difficult to meet extreme environment and precision requirements.

Method used

Semiconductive strontium titanate ceramics are prepared by treating niobium element doping and nitrogen. Specific steps include preparing niobium doped strontium titanate powder, preparing ceramic samples by solid phase sintering, and annealing to improve its flexural electrical properties.

Benefits of technology

It significantly improves the flexural electrical properties of strontium titanate ceramics, and realizes the transformation of ceramic materials from insulators to semiconductors, suitable for wide temperature ranges and extreme environments. Compared with single crystal materials, ceramic materials are cheap, simple in preparation and wide application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751053A_ABST
    Figure CN119751053A_ABST
Patent Text Reader

Abstract

The invention relates to the field of functional materials, and discloses a preparation method and application of semiconducting strontium titanate ceramic, and the method comprises the following steps: preparing a ceramic blank from niobium-doped strontium titanate powder; according to the preparation method, the niobium-doped strontium titanate powder is directly prepared, then solid-phase sintering and annealing treatment are carried out, the ceramic sample can be obtained, compared with a traditional preparation method, the process is simpler and clearer, and the preparation method is suitable for large-scale industrial production. And the preparation cost is reduced. Through niobium element doping and nitrogen treatment, the ceramic material can be converted into a semiconductor from an insulator, and meanwhile, the high flexoelectric property is obtained. Compared with a single crystal material, the ceramic material is low in cost, simple in preparation method and wide in application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of functional materials, and in particular to a preparation method and application of semiconductor strontium titanate ceramics. Background Art

[0002] Electromechanical coupling materials are a type of functional materials that can realize the mutual conversion of mechanical energy and electrical energy, and are widely used in the field of aerospace. Electromechanical coupling effects mainly include piezoelectric effect, electrostrictive effect, flexoelectric effect research, etc., among which piezoelectric effect is the most widely used. However, with the increasingly complex service environment and the precision and miniaturization of devices, common piezoelectric materials are gradually unable to meet the needs of extreme environments and precision due to their inherent shortcomings. First, the piezoelectric effect only exists in non-centrosymmetric materials. Among the 32 crystal point group structures, only 20 have piezoelectricity, which limits the selection range of piezoelectric materials. Secondly, the widely used piezoelectric materials are polarized ferroelectric ceramic materials. When the ambient temperature is higher than its phase transition temperature, such materials will undergo phase transition and depolarization, resulting in device failure. In addition, high piezoelectric coefficient materials such as lead zirconate titanate (PZT) will pollute the environment. For environmental protection requirements, most countries have begun to restrict the use of lead-containing materials. Therefore, the development of electromechanical coupling materials with high electromechanical coupling performance and applicable to a wide temperature range has important scientific significance and engineering application value. As a new type of electromechanical coupling effect, the flexoelectric effect refers to the polarization phenomenon caused by strain gradient. Compared with the piezoelectric effect, the flexoelectric effect has the advantages of a wide range of material selection and a wide temperature range. In addition, since the flexoelectric effect is positively correlated with the strain gradient, when the material size is reduced to the micro-nano scale, its flexoelectric effect will be significantly enhanced, and it has obvious size dependence. However, for general dielectric materials, the flexoelectric coefficient is about 10 -10 C / m-10 -11 C / m, the performance is relatively weak. Studies have found that semiconductor materials have high flexoelectric coefficients. Therefore, cubic strontium titanate materials are selected, and niobium doping and nitrogen treatment are used to introduce additional electrons and oxygen vacancies, so that it is transformed from an insulator to a semiconductor, which significantly improves the flexoelectric coefficient of strontium titanate ceramics. The flexoelectric effect is a mechanoelectric coupling effect induced by strain gradient electric polarization. Studies have found that semiconductor materials have high flexoelectric coefficients, but current research is limited to single crystal materials, and ceramic materials are not involved. Summary of the invention

[0003] In order to overcome the defects of the above-mentioned prior art, the purpose of the present invention is to provide a preparation method and application of semiconductor strontium titanate ceramics to solve the technical problem of low flexoelectric properties of semiconductor strontium titanate ceramics prepared in the prior art.

[0004] The present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing a semiconductor strontium titanate ceramic, comprising: A ceramic embryo body is prepared by using niobium-doped strontium titanate powder; The prepared ceramic embryo is made into a ceramic sample by solid phase sintering, and then the ceramic sample is annealed to obtain a semiconductor strontium titanate ceramic.

[0005] Specifically, the specific preparation process of niobium-doped strontium titanate powder is as follows: The powders of strontium carbonate, titanium dioxide and niobium oxide are dried, and the dried powders of strontium carbonate, titanium dioxide and niobium oxide are mixed with niobium element doping ratio according to stoichiometric ratio to obtain a mixed raw material; the mixed raw material is ball-milled once, and the ball-milled mixed raw material is dried, and the dried mixed raw material is ground, sieved and then kept warm to obtain niobium-doped strontium titanate powder.

[0006] The doping ratio of niobium element in strontium carbonate, titanium dioxide and niobium oxide powder is 1:1:0.2%-0.6% mol.

[0007] Among them, the purity of strontium carbonate, titanium dioxide and niobium oxide powders is ≥99.8%, and the particle size is 100 nm-4μm.

[0008] In one ball milling process, the mass ratio of the mixed raw materials, the ball milling medium and the ball milling beads is 1:1:2-1:2:5.

[0009] Specifically, in the step of preparing a ceramic embryo body by using the prepared niobium-doped strontium titanate powder, the specific process is as follows: The fired niobium-doped strontium titanate powder is ball-milled for the second time to obtain particles with uniform particle size, and then 5 wt%-8 wt% polyvinyl alcohol solution is added and ground and stirred thoroughly to allow the polyvinyl alcohol solution to be evenly adsorbed on the surface of the particles. After stirring, the particles are placed in a ventilated and cool place for aging to obtain ceramic particles, which are then pressurized and demolded to obtain a pressed ceramic embryo.

[0010] Specifically, in the step of preparing a ceramic sample by solid phase sintering of a ceramic embryo, the specific process is as follows: The pressed ceramic body is placed in a muffle furnace, heated to 500-800 °C at a heating rate of 1 °C / min-5 °C / min, and kept warm for 1-5 h to discharge the binder. It is then heated to a sintering temperature of 1300-1400 °C, kept warm for 2-4 h, and then cooled to obtain a ceramic sample.

[0011] Specifically, the specific process of annealing the ceramic sample is as follows: The ceramic sample is placed in a tube furnace and heated to 800°C-1000°C for annealing at a heating rate of 3°C / min-10°C / min in a nitrogen environment to obtain a semiconductor strontium titanate ceramic.

[0012] In a second aspect, the present invention further provides a semiconductor strontium titanate ceramic obtained by the above-mentioned method for preparing a semiconductor strontium titanate ceramic.

[0013] In a third aspect, the present invention further provides an application of the semiconductor strontium titanate ceramic described above, wherein the semiconductor strontium titanate ceramic is applied to a sensor product.

[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention provides a method for preparing semiconductor strontium titanate ceramics, which comprises preparing niobium-doped strontium titanate powder; preparing a ceramic embryo by the prepared niobium-doped strontium titanate powder; preparing a ceramic sample by solid-phase sintering the ceramic embryo, and annealing the ceramic sample to complete the preparation of semiconductor strontium titanate ceramics. Compared with the traditional preparation method, the process is simpler and clearer, and the preparation cost is reduced. Through niobium doping and nitrogen treatment, the ceramic material can be transformed from an insulator to a semiconductor, and at the same time obtain high flexoelectric properties. Compared with single crystal materials, ceramic materials are low in cost, simple in preparation method, and have a wide range of applications.

[0015] Furthermore, by doping with niobium, the growth of ceramic grains can be inhibited, and the average grain size can be reduced from 13μm to 150nm. After grain refinement, the mechanical properties of ceramics will also be significantly enhanced.

[0016] Furthermore, the powders of strontium carbonate, titanium dioxide and niobium oxide are placed in a drying oven for drying, which can effectively remove moisture from the raw materials and avoid errors caused by different moisture contents during the weighing process.

[0017] Furthermore, adding anhydrous ethanol as a ball milling medium can not only improve the dispersibility of the powder, but also reduce the friction and wear during the ball milling process, thereby protecting the service life of the ball mill and agate balls.

[0018] Furthermore, the polyvinyl alcohol solution is added as a binder, and the powder is fully ground and stirred so that the binder is evenly adsorbed on the surface of the powder, which helps to form a strong bond between the powder particles and enhance the strength and stability of the ceramic body. The addition of the polyvinyl alcohol solution can also improve the fluidity of the powder, making it easier to fill the tiny gaps in the mold during the molding process, thereby improving the density and uniformity of the ceramic body.

[0019] Furthermore, ceramic particles with uniform particle size can be obtained through granulation and sieving. These particles can be more evenly distributed in the mold during molding, thereby optimizing the microstructure of the ceramic body and improving its mechanical and electrical properties.

[0020] Furthermore, in this embodiment, through the solid phase sintering process, the particles in the ceramic body are rearranged and fused at high temperature, so that the porosity is reduced, the density of the ceramic sample is significantly improved, and the mechanical properties and electrical properties of the ceramic are improved. During the sintering process, the grains in the ceramic body gradually grow and form a more compact and uniform microstructure. The optimization of this structure helps to reduce defects and stress concentration and improve the stability and reliability of ceramics. In the stage of heating and heat preservation, the adhesive in the ceramic body can be effectively discharged to prevent it from decomposing at high temperature to produce gas or residue, affecting the quality and performance of the ceramic. The heating rate and holding time of 1°C / min to 600°C and 3°C / min to 1400°C can ensure the uniformity and stability of the sintering process and avoid defects and performance degradation caused by too fast or too slow sintering rates. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Flow chart of the preparation method of semiconductor strontium titanate ceramics in an embodiment of the present invention; Figure 2 The microstructure diagram of strontium titanate ceramics with different niobium doping ratios in the embodiments of the present invention; Figure 3 1 is an XRD spectrum of strontium titanate ceramics with different niobium doping ratios in an embodiment of the present invention; Figure 4 is the flexoelectric coefficient μ of the strontium titanate ceramics with different niobium doping ratios at room temperature in the embodiment of the present invention 12 picture; Figure 5 is the flexoelectric coefficient μ of the niobium-doped strontium titanate ceramic at room temperature after nitrogen treatment in the embodiment of the present invention 12 picture; Figure 6 This is a diagram showing the mechanical properties of different niobium-doped strontium titanate ceramics in an embodiment of the present invention. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0023] The present invention is further described in detail below in conjunction with the accompanying drawings: The purpose of the present invention is to provide a preparation method and application of semiconductor strontium titanate ceramics to solve the technical problem of low flexoelectric performance of semiconductor strontium titanate ceramics prepared in the prior art.

[0024] Example 1 See also Figure 1 In one embodiment of the present invention, a method for preparing a semiconductor strontium titanate ceramic is provided, and the specific steps are as follows: Step 1, preparing niobium-doped strontium titanate powder; Specifically, in order to reduce the weighing error caused by moisture in chemicals, the powders of strontium carbonate SrCO3 (99.8%, Aladdin), titanium dioxide TiO2 (99.8%, Aladdin) and niobium oxide Nb2O5 (99.9%, McLean) were first placed in a drying oven and dried for 8 hours. Then, according to the stoichiometric ratio and the doping ratio of niobium element (doping ratio was 0.0%, 0.2%, 0.4%, 0.6%), the mass of each chemical raw material required for each component was calculated and weighed on a balance (accuracy was 0.0001 g). The weighed raw materials were then poured into a polytetrafluoroethylene ball milling jar filled with agate balls, anhydrous ethanol was added as the ball milling medium, and the mass ratio of mixed powder: anhydrous ethanol: ball milling beads was about 1:2:2, and ball milling was performed on a planetary ball mill; After ball milling, the raw materials were placed in an evaporating dish and dried at 90 °C for 8 h. The dried powder was ground and sieved, poured into a crucible, and kept at 1100 °C for 2 h to obtain niobium-doped strontium titanate powder.

[0025] In this embodiment, the purity of strontium carbonate, titanium dioxide and niobium oxide powders is ≥99.8%, and the particle size is 100 nm.

[0026] In this embodiment, the powders of strontium carbonate, titanium dioxide and niobium oxide are placed in a drying oven and dried for 8 hours, which can effectively remove moisture from the raw materials and avoid errors caused by different moisture contents during the weighing process.

[0027] A high-precision balance (accuracy of 0.0001 g) was used for weighing to ensure the accuracy of the raw materials.

[0028] The mass of each raw material is accurately calculated based on the stoichiometric ratio and the niobium doping ratio (0.0%, 0.2%, 0.4%, 0.6%), ensuring the accurate ratio between the reactants, which is conducive to the generation of niobium-doped strontium titanate powder with the expected structure.

[0029] In this embodiment, a planetary ball mill is used for ball milling. Through the combined action of agate balls and anhydrous ethanol, the raw material powders can be effectively mixed and dispersed in the medium, thereby avoiding the occurrence of agglomeration.

[0030] The shear force and impact force during the ball milling process help to destroy the surface structure of the raw material particles, increase their specific surface area, and thus improve the reaction activity.

[0031] In this embodiment, adding anhydrous ethanol as the ball milling medium can not only improve the dispersibility of the powder, but also reduce the friction and wear during the ball milling process, thereby protecting the service life of the ball mill and the agate balls.

[0032] The appropriate powder: anhydrous ethanol: ball milling beads mass ratio (about 1:2:2) ensures the ball milling effect while improving the quality and purity of the powder.

[0033] In this embodiment, the dried powder is kept at 1100° C. for 2 hours, which can promote a sufficient chemical reaction between the raw materials to generate niobium-doped strontium titanate powder with good crystallinity.

[0034] High temperature treatment can also remove residual organic matter and impurities in the powder, further improving its purity and quality.

[0035] In this embodiment, by precisely controlling the doping ratio of the niobium element and the heat treatment conditions, the performance of the strontium titanate powder can be regulated, such as changing its conductivity, dielectric properties, etc., so as to meet different application requirements.

[0036] Step 2, preparing a ceramic body using the prepared niobium-doped strontium titanate powder; Specifically, the fired niobium-doped strontium titanate powder is subjected to secondary ball milling to obtain a powder with uniform particle size, and then a 5wt% polyvinyl alcohol solution is added, and the powder is fully ground and stirred so that the adhesive is evenly adsorbed on the surface of the powder. During the granulation process, the powder is sieved to ensure that the particles are uniform in size. After the granulation is completed, the particles are placed in a ventilated and cool place for aging for 24 hours, a certain amount of ceramic particles are weighed, poured into a mold, and then pressurized to 150MPa under a manual tablet press for 5 minutes, and a pressed ceramic embryo is obtained after demolding.

[0037] In this embodiment, the fired niobium-doped strontium titanate powder is subjected to secondary ball milling, which can further refine the powder particles and make the particle size more uniform, which helps to obtain a more dense and uniform ceramic embryo during the molding process. Powders with uniform particle sizes are easier to fill the mold during molding, reducing the formation of voids and defects, thereby improving molding efficiency and the quality of the ceramic embryo.

[0038] In this embodiment, 5wt% polyvinyl alcohol solution is added as a binder, and the powder is fully ground and stirred so that the binder is evenly adsorbed on the surface of the powder, which helps to form a firm bond between the powder particles and enhance the strength and stability of the ceramic body. The addition of polyvinyl alcohol solution can also improve the fluidity of the powder, making it easier to fill the tiny gaps in the mold during the molding process, thereby improving the density and uniformity of the ceramic body.

[0039] In this embodiment, ceramic particles with uniform particle size can be obtained through granulation and sieving. These particles can be more evenly distributed in the mold during molding, thereby optimizing the microstructure of the ceramic body and improving its mechanical and electrical properties.

[0040] Step 3, preparing a ceramic sample by solid phase sintering the ceramic embryo, and annealing the ceramic sample to complete the preparation of the semiconductor strontium titanate ceramic.

[0041] Specifically, the ceramic preparation was completed by using the traditional sintering method. The pressed ceramic body was placed in a muffle furnace and heated to 600°C at a heating rate of 1°C / min and kept at this temperature for 3 hours to allow the adhesive to be discharged as completely as possible. The temperature was then raised to 1400°C at a heating rate of 3°C / min, kept at this temperature for 3 hours, and then cooled with the furnace to obtain a ceramic sample.

[0042] Specifically, the fired ceramic is placed in a tubular furnace, heated to 900° C. and annealed for 2 hours in a nitrogen environment.

[0043] In this embodiment, through the solid phase sintering process, the particles in the ceramic embryo are rearranged and fused at high temperature, so that the porosity is reduced, the density of the ceramic sample is significantly improved, and the mechanical properties and electrical properties of the ceramic are improved. During the sintering process, the grains in the ceramic embryo gradually grow and form a more compact and uniform microstructure. The optimization of this structure helps to reduce defects and stress concentration and improve the stability and reliability of ceramics. In the stage of heating to 600°C and keeping warm for 3 hours, the adhesive in the ceramic embryo can be effectively discharged to prevent it from decomposing at high temperature to produce gas or residue, affecting the quality and performance of the ceramic. The heating rate and holding time of 1°C / min to 600°C and 3°C / min to 1400°C can ensure the uniformity and stability of the sintering process and avoid defects and performance degradation caused by too fast or too slow sintering rates.

[0044] In this embodiment, during the annealing process, the ceramic sample is kept at 900°C for 2 hours, which can effectively eliminate the residual stress and thermal stress generated during the sintering process, and improve the stability and crack resistance of the ceramic. Annealing can also promote the further transformation and optimization of the crystalline phase in the ceramic, making it more stable and uniform. This helps to improve the electrical properties and thermal stability of the ceramic. Annealing in a nitrogen environment can prevent the ceramic sample from reacting with oxygen in the air, resulting in surface oxidation or discoloration. At the same time, nitrogen can also play a protective role and reduce the mass loss of the sample during the annealing process.

[0045] In this embodiment, niobium is used as a donor doping to introduce extra electrons, and nitrogen treatment is used to introduce oxygen vacancies, reduce grain boundary resistance, and transform the ceramic sample from an insulator to a semiconductor. Tests have found that the flexoelectric coefficient of the treated strontium titanate ceramic is three orders of magnitude higher than that of pure strontium titanate ceramic.

[0046] Example 2 See also Figure 1 In one embodiment of the present invention, a method for preparing a semiconductor strontium titanate ceramic is provided, and the specific steps are as follows: Step 1, preparing niobium-doped strontium titanate powder; Specifically, in order to reduce the weighing error caused by moisture in chemicals, the powders of strontium carbonate SrCO3 (99.8%, Aladdin), titanium dioxide TiO2 (99.9%, Aladdin) and niobium oxide Nb2O5 (99.9%, McLean) were first placed in a drying oven and dried for 12 hours. Then, according to the stoichiometric ratio and the doping ratio of niobium element (doping ratio of 0.3% and 0.5%), the mass of each chemical raw material required for each component was calculated and weighed on a balance (accuracy of 0.0001 g). The weighed raw materials were then poured into a polytetrafluoroethylene ball mill filled with agate balls, anhydrous ethanol was added as the ball milling medium, and the mass ratio of mixed powder: anhydrous ethanol: ball milling beads was about 1:1:3, and ball milling was performed on a planetary ball mill; After ball milling, the raw materials were placed in an evaporating dish and dried at 90 °C for 8 h. The dried powder was ground and sieved, poured into a crucible, and kept at 1100 °C for 2 h to obtain niobium-doped strontium titanate powder.

[0047] Step 2, preparing a ceramic body using the prepared niobium-doped strontium titanate powder; Specifically, the fired niobium-doped strontium titanate powder is subjected to secondary ball milling to obtain a powder with uniform particle size, and then 8wt% polyvinyl alcohol solution is added, fully ground and stirred, so that the adhesive is evenly adsorbed on the surface of the powder. During the granulation process, in order to ensure that the particles are uniform in size, the powder is sieved. After the granulation is completed, the particles are placed in a ventilated and cool place for aging for 24 hours, a certain amount of ceramic particles are weighed, poured into the mold, and then pressurized to 150MPa under a manual tablet press for 5 minutes, and the pressed ceramic embryo is obtained after demolding.

[0048] Step 3, preparing a ceramic sample by solid phase sintering the ceramic embryo, and annealing the ceramic sample to complete the preparation of the semiconductor strontium titanate ceramic.

[0049] Among them, the traditional sintering method is used to complete the preparation of ceramics. The pressed ceramic body is placed in a muffle furnace and heated to 500°C at a heating rate of 3°C / min and kept warm for 2 hours to allow the adhesive to be discharged as completely as possible. Then the temperature is raised to 1350°C at a heating rate of 4°C / min, kept warm for 2 hours, and then cooled with the furnace to obtain a ceramic sample. The fired ceramic is placed in a tubular furnace and heated to 100°C for annealing for 2 hours in a nitrogen environment.

[0050] In summary, the present embodiment provides a method for preparing a semiconductor strontium titanate ceramic, by preparing niobium-doped strontium titanate powder; preparing a ceramic embryo by the prepared niobium-doped strontium titanate powder; preparing a ceramic sample by solid-phase sintering the ceramic embryo, and annealing the ceramic sample to complete the preparation of semiconductor strontium titanate ceramics. Through niobium doping, the conductive properties of strontium titanate ceramics can be effectively regulated to make it have semiconductor properties. The present invention directly prepares niobium-doped strontium titanate powder, and then obtains a ceramic sample through solid-phase sintering and annealing. Compared with the traditional preparation method, the process is simpler and clearer, and the preparation cost is reduced. Through niobium doping and nitrogen treatment, the ceramic material can be transformed from an insulator to a semiconductor, and at the same time obtains high flexographic electrical properties. Compared with single crystal materials, ceramic materials are low in cost, simple in preparation method, and have a wide range of applications.

[0051] In this embodiment, by doping niobium, the growth of ceramic grains can be suppressed, and the average grain size is reduced from 13 μm to 150 nm. After the grains are refined, the mechanical properties of the ceramics will also be significantly enhanced.

[0052] Example 3 This embodiment provides a semiconductor strontium titanate ceramic, which is obtained by the above-mentioned method for preparing a semiconductor strontium titanate ceramic.

[0053] In this embodiment, the semiconductor strontium titanate ceramic is doped with niobium, and the band structure of the strontium titanate ceramic is adjusted so that its conductivity is between that of a conductor and an insulator, that is, it has semiconductor properties. When this semiconductor strontium titanate ceramic is subjected to external stimuli, the concentration and mobility of the internal carriers will change, thereby changing its resistivity or generating an electrical signal. This change can be used to detect changes in the external environment or as a basic material for electronic devices. When the semiconductor strontium titanate ceramic is subjected to external force, a strain gradient will be generated inside it, thereby generating a flexoelectric effect. This effect causes the centers of positive and negative charges inside the ceramic to be relatively displaced, thereby generating polarized charges. By measuring the changes in this polarized charge, accurate detection and quantification of external forces can be achieved.

[0054] In this embodiment, the electrical conductivity of the semiconductor strontium titanate ceramic is significantly improved compared to the pure strontium titanate ceramic, which makes the material have a wider application prospect in the fields of electronic devices, sensors, etc.

[0055] Example 4 This embodiment also provides a method for testing the flexural electrical properties of semiconductor strontium titanate ceramics, and a flexural electrical properties test is performed on the semiconductor strontium titanate ceramics described above to obtain a flexural electrical signal.

[0056] The specific process is as follows: Silver electrodes were coated on the upper and lower surfaces of the semiconductor strontium titanate ceramic with silver paste, and wires were connected. After drying, flexural electrical testing was performed.

[0057] The flexural electric coefficient test was carried out by three-point bending. A sinusoidal force with a frequency of 1 Hz was applied to the center of the upper surface of the beam. The span of the three-point bending was L = 20 mm, the average strain gradient in the thickness direction of the sample is , where δ is the displacement of the sample center, a is the half length of the electrode. Use a charge amplifier and an oscilloscope to detect the polarization charge Q , electric polarization intensity P Can be P = Q / A. According to the strain gradient of the sample and the flexoelectric signal measured on the electrode, the transverse flexoelectric coefficient μ is obtained. 12 .

[0058] In this embodiment Figure 2 The SEM images of strontium titanate ceramics with different doping ratios, where (a) is strontium titanate ceramics; (b) is 0.2% doped strontium titanate ceramics; (c) is 0.4% doped strontium titanate ceramics; (d) is 0.6% doped strontium titanate ceramics. It can be seen that ceramics with high-density nanoscale grains have been successfully prepared, and the grain size distribution is uniform. Figure 3XRD diagrams of ceramics with different doping ratios. Figure 3 It can be seen that all samples have a tetragonal perovskite structure and no second phase is produced. Figure 4 The lateral flexoelectric coefficient of strontium titanate ceramics varies with the niobium doping ratio. When the niobium doping concentration is 0.4%, the flexoelectric coefficient is 94.7 nC / m, which is 30 times higher than that of pure strontium titanate ceramics. After nitrogen treatment, the flexoelectric coefficient of strontium titanate ceramics with a doping ratio of 0.4% increases to 3573.6 nC / m, which is three orders of magnitude higher than that of pure strontium titanate ceramics. Figure 5 As shown. The mechanical properties of different niobium-doped strontium titanate ceramics, such as Figure 6 shown.

[0059] In this embodiment, a semiconductor strontium titanate ceramic with high density and uniform grain size was successfully prepared, and its flexoelectric properties were accurately evaluated by the flexoelectric properties test method. The results show that both niobium doping and nitrogen treatment have a significant effect on the flexoelectric properties of the ceramic, and the strontium titanate ceramic with a doping ratio of 0.4% exhibits excellent flexoelectric properties after nitrogen treatment.

[0060] Example 5 This embodiment provides an application of the semiconductor strontium titanate ceramic described above, and applies the semiconductor strontium titanate ceramic to a sensor product.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a semiconductor strontium titanate ceramic, characterized in that: include: A ceramic embryo body is prepared by using niobium-doped strontium titanate powder; The prepared ceramic embryo is made into a ceramic sample by solid phase sintering, and then the ceramic sample is annealed to obtain a semiconductor strontium titanate ceramic.

2. The method for preparing a semiconductor strontium titanate ceramic according to claim 1, characterized in that: The specific preparation process of the niobium-doped strontium titanate powder is as follows: The powders of strontium carbonate, titanium dioxide and niobium oxide are dried, and the dried powders of strontium carbonate, titanium dioxide and niobium oxide are mixed with niobium element doping ratio according to stoichiometric ratio to obtain a mixed raw material; the mixed raw material is ball-milled once, and the ball-milled mixed raw material is dried, and the dried mixed raw material is ground, sieved and then kept warm to obtain niobium-doped strontium titanate powder.

3. The method for preparing a semiconductor strontium titanate ceramic according to claim 2, characterized in that: The niobium element doping ratio of the strontium carbonate, titanium dioxide and niobium oxide powders is 1:1:0.2%-0.6% mol.

4. The method for preparing a semiconductor strontium titanate ceramic according to claim 2, characterized in that: The purity of the strontium carbonate, titanium dioxide and niobium oxide powders is ≥99.8%, and the particle size is 100 nm-4 μm.

5. The method for preparing a semiconductor strontium titanate ceramic according to claim 2, characterized in that: In a ball milling process, the mass ratio of the mixed raw materials, the ball milling medium and the ball milling beads is 1:1:2-1:2:

5.

6. The method for preparing a semiconductor strontium titanate ceramic according to claim 1, characterized in that: In the step of preparing a ceramic embryo body by using the prepared niobium-doped strontium titanate powder, the specific process is as follows: The fired niobium-doped strontium titanate powder is ball-milled for the second time to obtain particles with uniform particle size, and then 5wt%-8wt% polyvinyl alcohol solution is added, and the mixture is fully ground and stirred so that the polyvinyl alcohol solution is evenly adsorbed on the surface of the particles. After stirring, the particles are placed in a ventilated and cool place for aging to obtain ceramic particles, which are then pressurized and demolded to obtain a pressed ceramic embryo.

7. The method for preparing a semiconductor strontium titanate ceramic according to claim 1, characterized in that: In the step of preparing the ceramic sample by solid phase sintering of the ceramic embryo, the specific process is as follows: The pressed ceramic body is placed in a muffle furnace, heated to 500-800 °C at a heating rate of 1 °C / min-5 °C / min, and kept warm for 1-5 h to discharge the binder. It is then heated to a sintering temperature of 1300-1400 °C, kept warm for 2-4 h, and then cooled to obtain a ceramic sample.

8. The method for preparing a semiconductor strontium titanate ceramic according to claim 1, characterized in that: The specific process of annealing the ceramic sample is as follows: The ceramic sample is placed in a tube furnace and heated to 800°C-1000°C for annealing at a heating rate of 3°C / min-10°C / min in a nitrogen environment to obtain a semiconductor strontium titanate ceramic.

9. A semiconductor strontium titanate ceramic, characterized in that: The semiconductor strontium titanate ceramic is obtained by the preparation method of any one of claims 1 to 8.

10. An application of the semiconductor strontium titanate ceramic according to claim 9, characterized in that: The semiconductor strontium titanate ceramic is applied to sensor products.

Citation Information

Patent Citations

  • Producing semiconductor strontium titanate particles

    CH669951A5

  • Niobium or niobium-lanthanum doped strontium titanate nano powder and preparation method and application thereof

    CN104973621A

  • Preparation method of niobium-doped barium titanate ceramic material capable of improving flexoelectric property

    CN117819962A

  • Doped strontium titanate

    GB2015977A

  • Production of semiconductive srtio3 particle and high-dielectric constant ceramic

    JP1987235214A